The Students’ Perception of Google Classroom in English Phonology Class - Much Deiniatur (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2020)
The study aims to investigate students’ perceptions on the use of Google Classroom in English Phonology Class, English Department in an Islamic College, Indonesia. This research used a survey study. The participant of this research was 48 students enrolled in the English Phonology Class. They were asked to fill out an online survey through the Google Forms at the end of the course to investigate their perceptions on the use of Google Classroom. The result shows that students have a positive perception of the use of Google Classroom in English Phonology Class. Future studies are expected to conduct research and development on the content of the material used for google classroom.